THE MOVEMENT OF STRUGGLING OF NEO-COMMUNISM RISING IN POST-REFORM (A Study of Ideology and Struggle Movement in Indonesia) - Ahmad Suhaimi; Pagar Pagar (State Islamic University of North Sumatra Indonesia, 2019)
The trauma of the nation's children has not been able to recover from the betrayal many times for the same cause by the PKI. The events of Madiun in 1948, and G.30S PKI became menumental witnesses of the martyrdom of thousands of scholars and students of PKI's savagery, as well as the death of the nation's heroes because they were kidnapped, slaughtered, sliced and dragged into crocodile holes. The reform era, which tends to care about human rights, democratization, and freedom of thought, expression and opinion, has been misused for the growth and re-emergence of communism in Indonesia. Thus the research was proposed: